An improved Fully Homomorphic Encryption model based on N-Primes - Mohammed, Mohammed Anwar; Abed, Fadhil Salman (Kurdistan Journal of Applied Research, 2019)
Cloud computing is the provision of computing services over the internet, which provides unlimited computing capabilities to its users. Cloud Service Providers (CSP) in the distanced places helps the users such as businesses and individuals to use its software and hardware means. The physical distance between the users and providers allows third parties to be capable of accessing the data which threats the privacy of the users. Thus, its security is the main concern when it comes to transform data from a locally owned storage to cloud storage. Cloud providers are required to save an encrypted version of user’s data on their storage. The traditional encryption schemes have been used for data encryption prior to sending them to the provider. Thought, the secret key has to be provided by the users to the server so as to decrypt the information prior to the requirement of calculations. Therefore, the traditional cryptographic schemes cannot be used to process cloud’s data. After the encryption of the information data are revealed to calculation in clouds, so confidentiality is not guaranteed and this result in difficulty in using cloud. In Homomorphic Encryptions calculation on ciphertext can be performed with no need for decryption. This paper, develops and designs a new mathematical model to achieve the characteristics of the Fully Homomorphic Encryption. The proposed model’s security depends on the problem of Factorization the integers to their primary numbers. In this paper, instead of dealing with two prime numbers it is expanded to deal with n prime numbers. The security of the presumptive algorithm to be more efficient in front of the security challenges facing cloud computing. What distinguishes this proposed system is that it deals with the explicit text after converting it to the ASCII code instead of converting it to the binary system as it is in the existing systems, thus providing speed in the encryption process and returns the encryption.